Predicting the Sound Insulation of Lightweight Sandwich Panels. Issue 3 (September 2013) - Davy, John L.; Cowan, Andre; Pearse, John R.; Latimer, Michael
The sound insulation of three sandwich panels was modelled using simple sound insulation prediction methods, but the agreement between theory and experiment was not very good. The effective Young's modulus was determined over a wide frequency from the resonant frequencies of three beams of different lengths. The effective Young's modulus was found to reduce with increasing frequency as has been predicted in the literature. This decrease is due to the core starting to shear rather than bend because its Young's modulus is much less than the Young's moduli of the skins. Unfortunately the agreement between theory and experiment was still not very good. This is because many of the prediction frequencies occur in the critical frequency dip because of the variation of the Young's modulus with frequency.